Infants and toddlers : development and program planning - Deiner, Penny Low. (Fort Worth, TX : Harcourt Brace College Publishers, 1997)
This book brings together current research and theories about how infants grow and develop, and applies that information to their early care and education settings.
Includes bibliographical references (p.509-537) and indexes.
Keywords: Infants -- Growth; Infants -- Development; Infants -- Care; Child development; Exercise for children; Children -- Language; Early childhood education -- Curricula -- United States